Photofunctionalization of anodized titanium surfaces using UVA or UVC light and its effects against Streptococcus sanguinis. Issue 6 (3rd November 2017) - Jain, Sakshi; Williamson, Randall S.; Marquart, Mary; Janorkar, Amol V.; Griggs, Jason A.; Roach, Michael D.
Abstract: UV light preirradiation of anodized titanium oxide layers has recently been shown to produce a photocatalytic effect that may reduce early bacterial attachment on titanium surfaces. Streptococcus species have been identified as primary early colonizers and contribute to early biofilm formation on dental implant surfaces. Anodized layers with primarily amorphous, primarily anatase, primarily rutile, and mixtures of anatase and rutile phase oxides were preirradiated with UVA or UVC light for 10 min. Nanoscale surface roughness and pre‐ and post‐UV‐irradiated wettability were measured for each anodization group. Sample groups were subjected to streptococcus sanguinis for a period of 24 h. Bacterial attachment and killing efficacy were measured and compared to the corresponding non‐UV control groups. UVA treatments showed trends of at least a 20% reduction in bacterial attachment regardless of the crystallinity, or combination of oxide phases present. Anodized layers consisting of primarily anatase phase on the outermost surface were shown to have a killing efficacy of at least 50% after preirradiation with UVA light. Anodized layers containing disperse mixtures of anatase and rutile phases at the outermost surface showed at least a 50% killing efficacy after pre‐irradiation with either UVA or UVC light. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2284–2294, 2018.